Implementasi Algoritma Clustering DBSCAN terhadap Pola Navigasi Pengguna di Perpustakaan Digital untuk Mengungkap Zona Buta Akses Informasi dan Optimalisasi Antarmuka Sistem - Sherly Rosa Anggraeni (Universitas Budi Luhur, 2025)
Advances in information technology have encouraged the transformation of libraries to digital form, increasing accessibility, but not all collections can be reached equally by users. This study aims to identify user navigation patterns and information access blind zones in the INLISLite digital library system using the DBSCAN clustering algorithm. Simulation log data representing common user exploration sessions were analyzed through the stages of one-hot representation, density-based clustering, and two-dimensional visualization with PCA. The results showed the formation of six main clusters with different navigation behavior characteristics and 15% of the sessions were classified as outliers. Pages such as “Advanced Search” and “Favorites” were detected as blind zones because they were not reached in most sessions. These findings indicate a failure of the interface to bridge users to the entire spectrum of information. Recommendations of navigation redesign, contextual pop-up of hidden content, and adaptive interface approaches were proposed as solutions. The DBSCAN-based approach proved effective for evaluating the effectiveness of digital information systems in terms of user behavior, and has the potential to be applied in the development of more responsive and inclusive digital libraries.